2011
DOI: 10.1088/1751-8113/44/22/225203
|View full text |Cite
|
Sign up to set email alerts
|

The curvature of semidirect product groups associated with two-component Hunter–Saxton systems

Abstract: Abstract. In this paper, we study two-component versions of the periodic Hunter-Saxton equation and its µ-variant. Considering both equations as a geodesic flow on the semidirect product of the circle diffeomorphism group Diff(S) with a space of scalar functions on S we show that both equations are locally well-posed. The main result of the paper is that the sectional curvature associated with the 2HS is constant and positive and that 2µHS allows for a large subspace of positive sectional curvature. The issues… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The 2-HS equation has attracted much attention in the past and it has been studied extensively by many authors [9,10,11,12,13,14,15,16,17]. In a series papers by Wunsch, he studies the local and global weak solutions for the periodic 2-HS equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-HS equation has attracted much attention in the past and it has been studied extensively by many authors [9,10,11,12,13,14,15,16,17]. In a series papers by Wunsch, he studies the local and global weak solutions for the periodic 2-HS equation.…”
Section: Introductionmentioning
confidence: 99%
“…The local wellposedness and wave-breaking was studied by Moon and Liu [14]. The geometric property of the 2-HS equation was investigated in [16]. The two-component Hunter Saxton system is a particular case of the Gurevich Zybin system pertaining to nonlinear one-dimensional dynamics of dark matter as well as nonlinear ion-acoustic waves (cf.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the system describes the geodesic flows on semidirect product Lie group of diffeomorphism group D s .S/ and the space of scalar functions on S [17,18]. One can readily verify that it also describes pseudo-spherical surfaces [19], namely there exist forms associated with the system…”
Section: Y Zhangmentioning
confidence: 94%
“…System can be viewed as a mid‐way one between the two‐component Camassa–Holm system and two‐component Hunter–Saxton system, which admits the Lax‐pair alignedrightφxxleft=λm+λ2ρ2φ,rightrightφtleft=12λuφx+12uxφ. It was shown that the system describes the geodesic flows on semidirect product Lie group of diffeomorphism group scriptDs(double-struckS) and the space of scalar functions on double-struckS . One can readily verify that it also describes pseudo‐spherical surfaces , namely there exist forms associated with the system alignedrightω1left=14λ2MathClass-open(ρ21MathClass-close)+12λm+1dx+14λ2uMathClass-open(1ρ2MathClass-close)14λ1+2umρ2+2ux+12μudt,rightrightω2left=…”
Section: Introductionmentioning
confidence: 99%
“…When ρ ≢0 and γ i =0( i = 1,2), Constantin and Ivanov considered the peakon solutions of the Cauchy problem of system . In paper , Wunsch studied the Cauchy problem of two‐component periodic Hunter–Saxton system; see also .…”
Section: Introductionmentioning
confidence: 99%